Synthesis and Characterisation of Ferrite-Ferroelectric Composites with Rare Earth Substitution - Rani, Renu (My University, 2013)
The materials exhibiting at least two of the three properties (ferroelectricity, ferromagnetism and ferroelasticity) are termed as multiferroic materials. Magnetoelectric materials, which simultaneously exhibit ferroelectricity and ferromagnetism, have been drawing attention of the researchers due to their multifunctionality and thereby finding applications in a number of devices. Researchers found a lot of interest in these materials not only because they have the properties of their parent compounds i.e. ferrite and ferroelectric phase, but also due to their unique property, Magnetoelectric (ME) effect. The magnetoelectric effect is a coupled two-field effect in which induction of electric polarization by applying an external magnetic field and induction of magnetic polarization by applying an external electric field. Magnetoelectric materials can be realized in single phase and two phases (composite form). In single phase materials, ME is due to the coupling of magnetic and electric orders but almost all single phase magnetoelectric materials have temperature constraint i.e. they show ME effect at low temperatures and the effect is weak. Due to this, these materials have very limited use.To overcome the deficiency of single-phase multiferroics and to provide new approach to the magnetoelectric coupling mechanisms, recent work concentrates on the class of composite-type magnetoelectric materials. In magnetoelectric composite the origin of magnetoelectric effect is due to mechanical coupling between magnetostriction effect in ferrite phase and piezoelectric effect in ferroelectric phase i.e. stress-strain coupling. These composite-type material have high ME coupling response even above room temperature and due to their high value of ME coefficients, these materials have various advantages over single-phase magnetoelectric materials.So many researchers are getting attracted towards the investigations of magnetoelectric composite materials not only due to their large value of ME coefficient but also due to their wide range of applications in electronic devices like sensors, wave guide, transducers, actuators, phase invertors, radio electronics, optoelectronics, microwave electronics, transducers in instrumentation and fiber communication technology. For the present work, composites of Ni-Zn ferrite (NZF) and barium strontium titanate (BST) were studied and efforts have been made to improve their dielectric, ferroelectric, piezoelectric, magnetic and magnetoelectric properties.
PHD, SPMS
Keywords: Magneto-electric composites; Ferroelectrics; Ferrite